Molecular characterization of Spanish patients with MECP2 duplication syndrome. Issue 4 (23rd February 2020) - Pascual‐Alonso, Ainhoa; Blasco, Laura; Vidal, Silvia; Gean, Esther; Rubio, Patricia; O'Callaghan, Mar; Martínez‐Monseny, Antonio F.; Castells, Alba Aina; Xiol, Clara; Català, Vicenç; Brandi, Nuria; Pacheco, Paola; et al.
Abstract: MECP2 duplication syndrome (MDS) is an X‐linked neurodevelopmental disorder characterized by a severe to profound intellectual disability, early onset hypotonia and diverse psycho‐motor and behavioural features. To date, fewer than 200 cases have been published. We report the clinical and molecular characterization of a Spanish MDS cohort that included 19 boys and 2 girls. Clinical suspicions were confirmed by array comparative genomic hybridization and multiplex ligation‐dependent probe amplification (MLPA). Using, a custom in‐house MLPA assay, we performed a thorough study of the minimal duplicated region, from which we concluded a complete duplication of both MECP2 and IRAK1 was necessary for a correct MDS diagnosis, as patients with partial MECP2 duplications lacked some typical clinical traits present in other MDS patients. In addition, the duplication location may be related to phenotypic severity. This observation may provide a new approach for genotype‐phenotype correlations, and thus more personalized genetic counselling. Abstract :